2022
DOI: 10.1111/1462-2920.16026
|View full text |Cite
|
Sign up to set email alerts
|

Into the darkness: the ecologies of novel ‘microbial dark matter’ phyla in an Antarctic lake

Abstract: Summary Uncultivated microbial clades (‘microbial dark matter’) are inferred to play important but uncharacterized roles in nutrient cycling. Using Antarctic lake (Ace Lake, Vestfold Hills) metagenomes, 12 metagenome‐assembled genomes (MAGs; 88%–100% complete) were generated for four ‘dark matter’ phyla: six MAGs from Candidatus Auribacterota (=Aureabacteria, SURF‐CP‐2), inferred to be hydrogen‐ and sulfide‐producing fermentative heterotrophs, with individual MAGs encoding bacterial microcompartments (BMCs), g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 155 publications
1
10
0
Order By: Relevance
“…Taxonomic a liation of the MAG using the genome classi er tool in the proGenomes database (900 000 genomes) resulted in no match, whereas phylogenetic analyses of the MAG using GTDB-tk pipeline [34] revealed deep branching within the Fibrobacterota, Chlorobiota and Bacteroidota (FCB) group, basal to Zixibacteria and Calditrichota phyla and within the "AABM5-125-24" phylum (Figure 2). A few members of the AABM5-125-24 phylum, also named Candidatus Electryoneota [40] have been identi ed as rare members of Ace Lake, Antarctica [17], which is a meromictic marine-derived lake like Lake A. However, analysis of the average amino acid identity (AAI, Figure 3) indicated a low similarity with most of Electryoneota/AABM5-125-24 genomes (<46%), including the Ace Lake representatives and a maximum of 57.5% of amino acid identity percentage with a genome recovered from Black Sea brackish waters (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taxonomic a liation of the MAG using the genome classi er tool in the proGenomes database (900 000 genomes) resulted in no match, whereas phylogenetic analyses of the MAG using GTDB-tk pipeline [34] revealed deep branching within the Fibrobacterota, Chlorobiota and Bacteroidota (FCB) group, basal to Zixibacteria and Calditrichota phyla and within the "AABM5-125-24" phylum (Figure 2). A few members of the AABM5-125-24 phylum, also named Candidatus Electryoneota [40] have been identi ed as rare members of Ace Lake, Antarctica [17], which is a meromictic marine-derived lake like Lake A. However, analysis of the average amino acid identity (AAI, Figure 3) indicated a low similarity with most of Electryoneota/AABM5-125-24 genomes (<46%), including the Ace Lake representatives and a maximum of 57.5% of amino acid identity percentage with a genome recovered from Black Sea brackish waters (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, structure of the operon, and more particularly the genes involved in electron transfer were variable, and included, in two other MAGs, genes coding the cytochrome b 6 f instead of dsrJOP. In addition to the potential for sulfate reduction, previous studies on Electryoneota lineages have reported a potential capability for aerobic respiration using high a nity cytochromes (cbb3-type) and sul de oxidation genes, suggesting a facultative anaerobic lifestyle [17]. None of these aerobic pathways were detected in the Tariuqbacter genome, suggesting a strictly anaerobic metabolism that differs from Antarctic Electryoneota lineages.…”
Section: Tariuqbacter Population Drives the Sulfur Cycle In Relict Ar...mentioning
confidence: 90%
See 1 more Smart Citation
“…GC content-read depth analysis was performed as described previously for Haloarchaea [39] and Ca. Chlorobium antarcticum [29].…”
Section: Gc Content Vs Read Depth Analysismentioning
confidence: 99%
“…Expeditions to retrieve samples from Ace Lake for metaproteogenomics first occurred in the austral summer 2006/2007, and subsequently in 2008/2009, with samples covering a complete seasonal cycle obtained in 2013-2015; biomass was collected by sequential size fractionation onto 3.0-, 0.8-and 0.1-μm pore-sized filters, with the metagenome data generated enabling the characterisation of diverse lake microorganisms [24,25,28,29,38,39]. The abundance of Synechococcus-like operational taxonomic units (OTUs) was assessed according to filter fraction, lake depth and season (Fig.…”
Section: Introductionmentioning
confidence: 99%